Le corps, enjeu de la guerre d’indépendance algérienne. La question sanitaire dans les camps de regroupement (1954-1962) - Fabien Sacriste (Les Cahiers de Framespa)
Algerian bodies were a major issue in the regroupment camps that were massively created by the French army during the War for Independence. Regroupments were then presented as the culmination of the « pacification » policy, as they aimed to both concentrate the supervisort actions over the Algerians, and transform society as well as individuals. But the sanitary and social outlook of those places offered a scathing contrast to the official speeches : social and economic insecurity, nutritional deficiencies and physiological misery, sanitary crisis and infant mortality characterized life in the camps. The regroupments then revealed the contradictions of the « pacification » policy, a set of actions supposed to promote the adhesion of the Algerian population to the French army’s cause, but which instead acted as a colonial violence that complicated its task and ultimately alienated Algerians.